Industrial Microbiology: Fundamentals and Applications - Agrawal (A K); Parihar (Pradeep) ("Agro House, Behind Nasrani Cinema Chopasani Road,Jodhpur - 342 002", 2005)
Industrial Microbiology
22.5
Keywords: Industrial Microbiology